Web of life and ways of life (Nóema, 2013)
The notion of bios is a key-concept in Foucault's research. In the studies about the ancient world, bios stands out as an ethic substance relevant to the practice, the control and the transformation of the self. It is worth investigating the analogies and the differences between the notion of bios as it is meant in the last lectures at the Collège de France and that of bios as a creative force, shared and plural, that we find in previous seasons of Foucault research. The issue of 'way of life' allows us to explore the ambivalences of this topic. In its singular/plural declination, bios raises questions about the common living, which results from the coexistence and sharing of different ways of life – bioi – that cut through the ground of the institutionalized relationships.